HISTORIOGRAPHY ANALYSIS OF HISTORY TEXT BOOK FROM NEERLANDOCENTRIC TO SCIENTIFIC - Darmawan, Wawan (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2010)
History text book is a historiography work for educational purpose. The historiography exposed in the history text book is definitely different from historiography of another scientific history book. The practical purpose of education becomes one of the important goals of composing the history text book. The history understood from history text book can do more than only developing the student’s historical awareness. The historical awareness can be detected in the attitude expressed by the students, such as their sense of nationality, partriotism, unity, willingness to sacrifice, etc. However, the history books composition, including the history text books, cannot avoid the spirit of the period it was written. According to the historiography development in Indonesia, the history text books has been written based on nederlandocentrism, indonesiacentrism, ideologism, and scientific, which are the result of how the spritit of a period affected the history text composition. This research analyse the historiography of history text books that are used in school, especialy in how these history text books appropriately reconstruct historical events with the spirit of a period and how it is composed based on scientific rules of history science.